Economic Effects of Deregulation - Using the Example of the Revised Trade and Crafts Code 2004 - Klaus Müller (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2016)
This paper examines the effects of the reform of the German Trade and Crafts Code of 2004, which removed entry requirements in 54 out of 95 crafts occupations. Since then, the Meister degree (advanced dual training degree) is no longer a prerequisite for opening a business in these occupations. The topic is highly relevant as there is an ongoing debate about the advantages and disadvantages of the regulation of occupations on the European level. The lack of suitable control group represents a major challenge of this analysis. Nevertheless, it can be argued that the goals brought forward by proponents of deregulation have not been achieved. Neither was there a major expansion of employment in the crafts sector, nor do we observe positive effects on training. – – Der Aufsatz untersucht die Auswirkungen der Reform der Handwerksordnung 2004 in Deutschland. Damals wurden 54 der 95 Handwerkszweige zulassungsfrei gestellt, d.h. für die Gründung eines Unternehmens ist seitdem keine Meisterprüfung mehr notwendig. Diese Untersuchung ist deshalb von aktueller Relevanz, weil auf europäischer Ebene breit über die Regulierung von Berufen diskutiert wird. Die Analyse stand deshalb vor einer großen Herausforderung, weil sich eine geeignete Kontrollgruppe nur mit Einschränkung finden ließ. Insgesamt kann jedoch festgestellt werden, dass sich die großen Hoffnungen der damaligen Befürworter der Reform nicht erfüllt haben. Weder ist es zu einer Beschäftigtenexpansion im Handwerk gekommen, noch können Impulse für Ausbildungsplätze beobachtet werden.
Keywords: 330; Skilled Crafts; Deregulation; Trade and Crafts Code